A Bird’s-Eye Overview of Leptin and Female Reproduction —with Mammalian Comparisons - Sadequllah Ahmadi; Takeshi Ohkubo (The Journal of Poultry Science)
Leptin, a key regulator of reproductive physiology, influences various processes in vertebrates, including oocyte proliferation, embryogenesis, the onset of puberty, ovarian function, and follicle development. In mammals, leptin affects steroidogenesis, folliculogenesis, and hormonal regulation through the hypothalamic-pituitary-gonadal axis. Instead, in avian species, leptin-controlled mechanisms are poorly understood, because birds do not produce leptin in adipocytes. In birds, leptin is expressed in the brain, pituitary glands, and gonads, where it enhances ovarian function and egg-laying performance, particularly during feed deprivation. In this review, we discuss and summarize the recently discovered role of leptin in regulating ovarian function during different life stages in birds and compare it with its function in mammals.